Effects of aging and exercise training on leg hemodynamics and oxidative metabolism in the transition from rest to steady-state exercise: role of cGMP signaling - Piil, Peter; Jørgensen, Tue Smith; Egelund, Jon; Rytter, Nicolai; Gliemann, Lasse; Bangsbo, Jens; Hellsten, Ylva; Nyberg, Michael (American journal of physiology. Regulatory, integrative and comparative physiology, 2018)
Aging is associated with slower skeletal muscle O 2 uptake (V̇o 2 ) kinetics; however, the mechanisms underlying this effect of age are unclear. Also, the effects of exercise training in elderly on the initial vascular and metabolic response to exercise remain to be elucidated. We measured leg hemodynamics and oxidative metabolism in the transition from rest to steady-state exercise engaging the knee-extensor muscles in young ( n = 15, 25 ± 1 yr) and older ( n = 15, 72 ± 1 yr) subjects before and after a period of aerobic high-intensity exercise training. To enhance cGMP signaling, pharmacological inhibition of phosphodiesterase 5 (PDE5) was performed. Before training, the older group had a slower ( P <0.05) increase in femoral arterial blood flow and leg vascular conductance in the transition from rest to steady-state exercise at low- and moderate-intensity compared with the young group. The rate of increase in leg V̇o 2 was, however, similar in the two groups as a result of higher ( P < 0.05) arteriovenous O 2 difference in the older group. Potentiation of cGMP signaling did not affect the rate of increase in blood flow or V̇o 2 in either group. Exercise training augmented ( P < 0.05) the increase in leg vascular conductance and blood flow during the onset of moderate-intensity exercise in both groups without altering V̇o 2 . These findings suggest that an age-related reduction in the initial vascular response to low- and moderate-intensity knee-extensor exercise is not limiting for V̇o 2 in older individuals. A lower blood flow response in aging does not appear to be a result of reduced cGMP signaling.